البعد الديني في أعمال أبي القاسم سعد الله - بن بردي, الزبير (University of Eloued جامعة الوادي, 2023)
ملخص: في إطار الاعتراف بجميل أساتذتنا الباحثين والمؤرخين الذين توفّتهم المنيّة، وتركوا لنا سجلا حافلا من أعمال متنوعة أنارت مكتباتنا العامة والخاصة، وكانت لنا بمثابة مصادر ومراجع أساسية نلجأ إليها ونستعين بها ونوظّفها في دراساتنا وبحوثنا الأكاديمية؛ خاصة في ميدان التاريخ، يأتي مقالي عن الأستاذ والمؤرخ أبي القاسم سعد الله، وإن كانت هناك كتابات عديدة عنه بعد وفاته، إلا أنّني أردت أن أبيّن أحد أهمّ الأبعاد التي تضمّنتها أعماله التي تنوّعت بين: التأليف والترجمة والتحقيق والتعليق، وشملت بدورها مواضيع متفرّقة، مثل: التاريخ، والأدب، والفكر والثقافة، والرحلات، والأعلام؛ ألا وهو البعد الديني. وهذا من باب العرفان والإحسان إليه في كل ما قدّمه للجامعة الجزائرية وللباحثين. Abstract: In showing gratitude to our scholars and historians who passed away, they left us with a huge record of various works that illuminated our public and private libraries, and served as essential sources and references for our knowledge and use in our studies, also in academic research; Especially in the field of history, my essay on Professor and historian Abu al-Qassim Saad allah comes, although there are many writings about him after his death, but I wanted to illustrate one of the most important dimensions of his work, which varied between: writing, translation, investigation and commentary, and in turn covered such disparate topics as history, literature, thought and culture, travels, and biographies ; This is the religious dimension. This is a matter of gratitude and benevolence in all his presentations to the University of Algeria and to the researchers.
مقال
Keywords: أبو القاسم ; سعد الله ; البعد ; الديني ; أعمال ; الإسلام ; الجزائر ; Abu al-Qassim ; Saad Allah ; Dimension ; Religious ; works ; Islam ; Algeria